PENINGKATAN KUALITAS KOLOSTRUM PADA IBU POSTPARTUM YANG DILAKUKAN PIJAT PAYUDARA DENGAN METODE OKETANI - Machmudah -; Nikmatul Khayati; Joko Teguh Isworo (Universitas Muhammadiyah Semarang, 2014)
Milk production is influenced by hormonal factors, dietary intake, maternal psychological condition, frequency of feeding infants, consumption of drugs / hormonal contraceptives and breast care (Kompas, 2013). One method is to do a breast care breast massage with Oketani method. Oketani massage can increase milk production and excretion are closely related tothe development and growth of the baby (Foda, et al, 2004). Machmudah (2013) explains that the combination of massage oketani and oxytocin can increase milk production were seen in breastfed infants frequency parameters, ferkuensi bowel and bladder. This study aims to determine how the quality of the colostrum before and after the massage oketani. This research is a quasi experimental design is used with a pre post test design with control group. Statistical analysis showed that there are significant differences between the protein content of colostrum before the massage after oketani (p = 0.002) and no significant difference betweenthe carbohydrate content of colostrum before the massage after oketani (p = 0.96).